Increasing Photocatalytic Stability and Photocatalytic Property of Polyaniline Conductive Polymer - Dogan, Deniz; Taş, Recep; Can, Muzaffer; Taş, Recep (Springer Int Publ Ag, 2020)
This study aims to enhance the photocatalytic properties and stability of polyaniline (PANI) by preparing polyaniline-metal oxide composites. Polyaniline and polyaniline-metal oxide composites were synthesized via chemical polymerization method and characterized by using scanning electron microscopy, X-ray diffraction (XRD), energy-dispersive X-ray analysis, and Fourier transform infrared spectrometry. The morphological characteristics of the polymers synthesized in media with and without metal oxide are quite different from each other. These differences are due to the presence of metal oxides in the polymer structure, and the interactions between PANI-metal oxides, as mentioned in the XRD interpretations. The photocatalytic properties of polyaniline and each polyaniline-metal oxide composite were investigated using methylene blue (MB) under UV light and in the dark. (MB is one of the pollutant dyes found in wastewater.) The findings showed that photocatalytic property and stability of polyaniline can be enhanced by preparing the polyaniline-metal oxide composites. TheE(g)values of the selected metal oxides are around 3 eV values. The metal oxides, having the 3 eV energy bandgap range, exhibit better photocatalytic properties. [GRAPHICS] .
Keywords: Photocatalyst; Polyaniline; Polyaniline-Metal Oxide Complex; Methylene Blue